2018
DOI: 10.1136/bmjopen-2017-019613
|View full text |Cite
|
Sign up to set email alerts
|

Community-based health insurance and healthcare service utilisation, North-West, Ethiopia: a comparative, cross-sectional study

Abstract: ObjectivesThe objective of this study was to compare differences in healthcare utilisation between community-based health insurance member households and non-member households and to identify factors for community-based health insurance enrolment in South Achefer District.DesignComparative, cross-sectional study.SettingsCommunity-based.ParticipantsA total of 652 selected households (326 insured and 326 uninsured households) participated in the study.MethodsA two-sample t-test (for proportions) and χ2(for categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
58
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(81 citation statements)
references
References 21 publications
15
58
3
1
Order By: Relevance
“…Marriage was also well articulated as a determinant for CBHI utilization. Being married was a positive factor to the WTJ to CBHI [23,37] and enrolment in the scheme [20,43,47,62]. According to family/household size, in most studies, it was a positive predictor for CBHI utilization [1, 18, 20, 22, 23, 37-39, 41, 42, 44-51, 62].…”
Section: Demographic and Socio-economic Factorsmentioning
confidence: 99%
See 4 more Smart Citations
“…Marriage was also well articulated as a determinant for CBHI utilization. Being married was a positive factor to the WTJ to CBHI [23,37] and enrolment in the scheme [20,43,47,62]. According to family/household size, in most studies, it was a positive predictor for CBHI utilization [1, 18, 20, 22, 23, 37-39, 41, 42, 44-51, 62].…”
Section: Demographic and Socio-economic Factorsmentioning
confidence: 99%
“…It was also negatively related with satisfaction of CBHI utilization [40,57]. Family size was positively associated with the WTJ in [1,23,37], WTP for [1,38,39,41,42], participation in [18,22], enrolment to [20,44,47,48,50,51,62], uptake of [45,46] and attitude of CBHI [49]; but negatively linked with [40,57] the scheme. Pointing to educational status of the household, twenty one studies reported that education was a positive determinant to CBHI utilization [1, 15, 18, 21, 23, 36, 38-44, 46-49, 57, 60-63] while two studies reported it as a negative predictor to scheme uptake [37,64].…”
Section: Demographic and Socio-economic Factorsmentioning
confidence: 99%
See 3 more Smart Citations